An exploration of students' lived experiences of using smartphones in diverse learning contexts using a hermeneutic phenomenological approach - Chan, Nee Nee *; Walker, Caroline; Gleaves, Alan (2015)
This study describes young people's experiences of using smartphones, by exploring what it means to acquire, possess, and create a purpose for these personal mobile devices within the complex and fluid contexts of formal and informal learning. Applying the principles and practices of hermeneutic phenomenology, this study's methods comprised the use of interviews and written reflective exercises. 12 youths ranging from 16 to 19 years old participated in 3 rounds of semi-structured interviews over a period of 6 months. The findings reveal that participants' smartphone appropriation is associated with self-identity and management of their image as it is perceived by salient others, including peers and teachers. Furthermore, the participants' smartphone use is dependant upon their perception of learning-value and subject to influences concerning the status of knowledge, from their peers, parents and the community at large. The findings would suggest that the significance that young people attach to this form of mobile device use and the transferability of such behaviours and uses across spaces, time and dimensions in learning contexts is critically a function of particular smartphone adoption at a cultural rather than pedagogic level. Further research including rich qualitative studies is suggested to better theorize the phenomenon of smartphone use in learning contexts through engaging with cultural and social perspectives.